Evidence for Sexual Dimorphism in the Plated Dinosaur Stegosaurus mjosi (Ornithischia, Stegosauria) from the Morrison Formation (Upper Jurassic) of Western USA - Saitta, Evan Thomas (PLOS ONE, 2015)
Conclusive evidence for sexual dimorphism in non-avian dinosaurs has been elusive. Here it is shown that dimorphism in the shape of the dermal plates of Stegosaurus mjosi (Upper Jurassic, western USA) does not result from non-sex-related individual, interspecific, or ontogenetic variation and is most likely a sexually dimorphic feature. One morph possessed wide, oval plates 45% larger in surface area than the tall, narrow plates of the other morph. Intermediate morphologies are lacking as principal component analysis supports marked size- and shape-based dimorphism. In contrast, many non-sex-related individual variations are expected to show intermediate morphologies. Taphonomy of a new quarry in Montana (JRDI 5ES Quarry) shows that at least five individuals were buried in a single horizon and were not brought together by water or scavenger transportation. This new site demonstrates co-existence, and possibly suggests sociality, between two morphs that only show dimorphism in their plates. Without evidence for niche partitioning, it is unlikely that the two morphs represent different species. Histology of the new specimens in combination with studies on previous specimens indicates that both morphs occur in fully-grown individuals. Therefore, the dimorphism is not a result of ontogenetic change. Furthermore, the two morphs of plates do not simply come from different positions on the back of a single individual. Plates from all positions on the body can be classified as one of the two morphs, and previously discovered, isolated specimens possess only one morph of plates. Based on the seemingly display-oriented morphology of plates, female mate choice was likely the driving evolutionary mechanism rather than male-male competition. Dinosaur ornamentation possibly served similar functions to the ornamentation of modern species. Comparisons to ornamentation involved in sexual selection of extant species, such as the horns of bovids, may be appropriate in predicting the function of some dinosaur ornamentation.